The pattern of international trade between Bangladesh and USA: Heckscher-Ohlin and Rybczynski analysis - Tanjina Akther; Liton Chandra Voumik; Md. Hasanur Rahman (Modern Supply Chain Research and Applications, 2022)
Purpose Research based on Bangladesh-US trade data examines the Heckscher-Ohlin model and the Rybczynski hypothesis in this study. Design/methodology/approach Ordinary least square (OLS) techniques are used in this study, which relies on data from the NBER International Trade and Geography Data and the UN Comtrade Database for the years 2018 and 2008. Findings The research shows that trade between the United States and Bangladesh follows Heckscher-Ohlin and Rybcyzinski's trade predictions. According to the study, since labor is in plentiful supply in Bangladesh, Bangladesh's labor-based sectors have a higher US labor-to-capital import shares than US capital-based industries. As Bangladesh has not changed significantly from a labor-based country since 2008, it retains the same pattern even though the share of US unskilled labor-based sectors imported from Bangladesh decreased in 2018. Originality/value The findings of this study have a wide range of implications for both trade theory and policy debates between Bangladesh and the United States.
Keywords: 650; Heckscher-Ohlin model; International trade; Romali's prediction; Rybczynski model